Analisisi Faktor-Fafktor Pembentuk Perilaku Ekonomi Syariah Pada Generasi Millennial Di Kabupaten Pringsewu - Fauzi Fauzi; Rita Irviani; Hidayatul Asra (Dinar Islamic Review, 2022)
The millennial generation has always been a hot topic for analysis because it has hedonic and consumptive characteristics in modern products and tries to find symbols of luxury in buying daily needs. Therefore, it is important to understand the role of several factors that are likely to shape their Islamic economic behavior, especially among the younger generation who are just working. The survey was conducted in Pringsewu Regency, Lampung, with more than 150 millennial generation respondents who had just started working (1-3 years) and were financially independent by using hauntedness as the main data collection tool. To find out what factors can actually shape Islamic economic behavior, a confirmatory factor analysis tool is used using the maximum likelihood estimation approach. The test results show that the construct of halal consumption consists of halal issues, Islamic branding, religious norms, consumer attitudes, product knowledge, halal product evaluation, and commitment, all of which are in the good classification.